Can archives feel? Emotions and trauma in archives - Parnica, Robert (Atlanti, 2024)
Purpose: This paper aims to investigate and elaborate on the definition of ‚emo-tional archival sources.‘. Emotional or trauma sources are the notion that some archivists and archival theoreticians have frequently used when dealing with sig-nificant violations of Human Rights, war destruction, and massive human suffer-ing. First, the author investigates how the archives and archivists can „feel“ the emotional „weight“ of those sources and if they can genuinely depict the trauma behind them by using proper and unbiased descriptive terms and expressions. The second level of analysis focuses on the ethical and professional problems of content description in archival praxis and the issues archivist face during their work. Method: The paper reviews available literature and analyzes the descriptions of several archival collections from the institutional archival catalog that raised professional and ethical concerns on bias and objectivity within the archival pro-fession. By comparing diverse emotional sources encapsulating various histor-ical and individual stories, archivists often stay on their own when deciding on ethical and other professional issues. The paper analyzes how emotional sources have multiple personal and societal meanings, as seen through some recent cul-tural criticism theories.Results: The emotional sources embody disturbing content in text, photos, and moving image materials that temporarily reduce our rational cognition during archival processing, especially description. Emotional and cognitive empathy are explained in the broader context of ethics of care. Archivists describe and la-bel metadata under the impact of emotional content and contextual information, but also archivists themselves are prone to emotional distress and emotional empathy, including secondary trauma. Conclusions: Emotional sources appear to be challenging to define and describe. Each trauma-related archival collection has a specific historical context requiring adequate descriptive language, terminology, and contextual information, making it difficult for archivists to make the right and long-term professional decisions.
Keywords: arhivi; arhivsko gradivo; čustva; čustvena empatija; etika; kognitivna empatija; sekundarna travma